Rancang Bangun Sistem Peminjaman Laboratorium Komputer Multi-Lokasi dengan Implementasi Real-time Locking dan Kebijakan No-Show Handling Berbasis Web di Sekolah Vokasi IPB - Widodo, Bayu; Renanti, Medhanita Dewi (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System; Vol 10 No 2 (2025): INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS (Desember 2025), 2025)
The digital transformation in higher education demands facility management systems that are efficient, transparent, and user-oriented. This is especially important for computer laboratory reservations, which are more complex technically and administratively than standard classroom bookings. At the Vocational School of IPB University, the manual reservation workflow caused schedule conflicts, limited visibility of availability, and difficulties in managing laboratories across multiple locations. This study aims to design and develop a web-based laboratory reservation system. The goal is to improve service effectiveness and user interaction by applying Design Science Research (DSR) methodology (a framework for creating and evaluating IT solutions) together with User-Centered Design (UCD) principles (methods focused on user needs and experience). System development included requirements analysis, Unified Modeling Language (UML—a system design notation), and UCD-based interface design, iterative prototyping, and both functional and usability evaluation. Black Box Testing (a method of checking that all features work as specified) showed 100% feature conformity, including a schedule-locking mechanism to prevent double booking. Usability was assessed using the System Usability Scale (SUS—a standard survey for usability), yielding a score of 82.3 (Excellent). This was accompanied by a 45% improvement in reservation efficiency compared to manual procedures. The findings demonstrate that the proposed system enhances administrative efficiency, improves transparency in room availability, and enhances the user experience. Academically, this work contributes a validated DSR–UCD model for usability-driven system development. Practically, it offers a scalable and replicable solution for managing laboratory reservations in multi-location vocational education environments.